Tide-Surge Interaction in the Pearl River Estuary: A Case Study of Typhoon Hato - Zheng, Peng; Li, Ming; Wang, Caixia; Wolf, Judith; Chen, Xueen; De Dominicis, Michela; Yao, Peng; Hu, Zhan (Frontiers in Marine Science, 2020)
In this study, the characteristics and mechanisms of tide-surge interaction in the Pearl River Estuary (PRE) during Typhoon Hato in August 2017 are studied in detail using a 3D nearshore hydrodynamic model. The wind field of Typhoon Hato is firstly reconstructed by merging the Holland parametric tropical cyclone model results with the CFSR reanalysis data, which enables the model to reproduce the pure astronomical tides and storm tides well; especially the distinctive oscillation pattern in the measured water levels due to the passage of the typhoon has been captured. Three different types of model runs are conducted in order to separate the water level variations due to the astronomical tide, storm surge and tide-surge interactions in the Pearl River Estuary. Results show the strong tidal modulation of the surge level, as well as alteration of the phase of surge which also changes the peak storm tidal level, in addition to the tidal modulation effects. In order to numerically assess the contributions of three nonlinear processes in the tide-surge interaction and quantify their relative significance, the widely used ``subtraction" approach and a new “addition" approach are tested in this study. The widely used “subtraction'' approach is found unsuitable for the assessment due to the ``rebalance" effect and thus a new “addition'' approach is proposed along with a new indicator to represent the tide-surge interaction, from which more reasonable results are obtained. Detailed analysis using the ``addition'' approach indicates that the quadratic bottom friction, shallow water effect and nonlinear advective effect play the first, second and third most important roles in the tidal-surge interaction in the estuary, respectively.